ANCIENT COMPONENTS AND RECENT EXPANSION IN THE EURASIAN HEARTLAND: INSIGHTS INTO THE REVISED PHYLOGENY OF Y-CHROMOSOMES FROM CENTRAL ASIA - Zhabagin, Maxat; Wei, Lan-Hai; Sabitov, Zhaxylyk; Ma, Peng-Cheng; Sun, Jin; Dyussenova, Zhanargul; Balanovska, Elena; Li, Hui; Ramankulov, Yerlan (Genes, 2022)
In the past two decades, studies of Y chromosomal single nucleotide polymorphisms (YSNPs) and short tandem repeats (Y-STRs) have shed light on the demographic history of Central Asia, the heartland of Eurasia. However, complex patterns of migration and admixture have complicated population genetic studies in Central Asia. Here, we sequenced and analyzed the Y-chromosomes of 187 male individuals from Kazakh, Kyrgyz, Uzbek, Karakalpak, Hazara, Karluk, Tajik, Uyghur, Dungan, and Turkmen populations. High diversity and admixture from peripheral areas of Eurasia were observed among the paternal gene pool of these populations. This general pattern can be largely attributed to the activities of ancient people in four periods, including the Neolithic farmers, Indo-Europeans, Turks, and Mongols. Most importantly, we detected the consistent expansion of many minor lineages over the past thousand years, which may correspond directly to the formation of modern populations in these regions. The newly discovered sub-lineages and variants provide a basis for further studies of the contributions of minor lineages to the formation of modern populations in Central Asia.
Keywords: Type of access: Open Access; Central Asia; Y-chromosome; paternal lineage; admixture